Direitos humanos, educação e cidadania LGBT: uma análise das ações do programa Brasil sem homofobia em João Pessoa/PB - Gomes, José Cleudo Gomes (2016)
Brazil have been experiencing a reconnaissance phase of the human rights of Lesbian, Gay, Bisexual and Transsexuals (LGBT), a segment of the population that has historically placed the margins of society, segregated from state actions and discriminated both in the private and public spheres. The focus of this study was to “Brasil Sem Homofobia (BSH): Program to Combat Violence and Discrimination against LGBT and Promotion of Homosexual Citizenship”, released in 2004 by the federal government. The program also included the direct participation of activists of the social movement and the government in its preparation. The perspective of this research was to analyze the actions implemented by Brasil Sem Homofobia program in the municipality of João Pessoa, from its transversality with public policies and interfaces to the LGBT movement. Thus, we analyzed the educational activities that have been implemented in thismunicipality, either by municipal public management as by higher education institutions and/or non-governmental organizations. The locus of the research was the city of João Pessoa, Paraíba, however, was identified that some actions benefited participants from other municipalities, although executed in the capital. The research was a qualitative study, taking as its starting point the bibliographical study and the literature review of academic publications related to the subject; authors who theorize about the LGBT movement and educational policies are its theoretical support. Then was performed a documentary analysis of the Brasil sem Homofobia (2004), Cadernos SECAD 4: Gender and Sexual Diversity in School (2007); Brazilian National Program of Human Rights (1996, 2002, 2009); the National Human Rights and Citizenship LGBT Plan (2009) and reports, publications, booklets and brochures produced locally by the institutions of government and civil society that have implemented actions in João Pessoa after the release of BSH between 2004 and 2009. We conducted semi-structured interviews with activists of LGBT organizations and activists, advisors and / or coordinating policies for LGBT projects and/or university extension. Finally, we noticed that public policies developed and implemented for the LGBT population in Brazil are contemporary to our times, conquered from the mobilization of the LGBT movement.